APPLICATION OF QASIR APPLICATION IN TRADING COMPANY CASH SALES ACCOUNTING INFORMATION SYSTEM: PENERAPAN APLIKASI QASIR DALAM SISTEM INFORMASI AKUNTANSI PENJUALAN TUNAI PERUSAHAAN DAGANG - Rika Kartika; Raden Irna Afriani; Sopan Sihabudin (Yayasan Education and Social Center, 2021)
The success of a company's business wheels is with a good and purposeful management pattern. This includes organized financial records. This study aims to determine the application of the QASIR application in the Cash Sales Accounting Information System. This study discusses about Cash Sale before and after using the Qasir application. This study uses a descriptive method with a qualitative approach. Sources of data in this study were obtained through purposive sampling and snowball sampling, with primary and secondary data types. Primary sources, data obtained through interviews and secondary sources obtained from record sales and inventory of store owners. From this study, the results obtained in the form of the Qasir application that purchase transaction data can be automatically stored as proof of cash receipts, and through the Qasir application one can easily find out the amount of profit from the sale